Satisfaction with work life balance programs and its relationship with work related outcomes - Cementina, Raquel S.; Pangan, Farida R.; Yabut, Katie Abigail C. (2005)
As a response to the rapid changes in the work environment, organizations continue to create programs that help employees attain work life balance. This study on call center employees explored the relationship of employee satisfaction with work-life balance programs on perceived job stress level, organizational commitment, and turnover intent. Results show that satisfaction with work life balance programs correlated negatively with perceived job stress level and positively with organizational commitment. However, it failed to show a relationship between satisfaction with work life balance programs and turnover intent. Implications of the study were discussed.
Includes bibliographical references (pages 134-137).